Pengaruh Persepsi Harga dan Kualitas Pelayanan Terhadap Kepuasan Pengunjung di Gor Bulutangkis Gunper Tasikmalaya - Fariz Rachmat Maulana (CV. Ulil Albab Corp, 2022)
The purpose of this study was to determine and analyze the effect of price perception and service quality on visitor satisfaction at GUNPER Badminton Tournament Tasikmalaya, either partially or simultaneously. The research method used is a quantitative method with a population survey approach in this study, visitors from GUNPER Badminton School in Tasikmalaya. Sampling was done by accidental sampling method which obtained a sample of 100 people. The technique used in this research is multiple linear regression. Price perception partially has a significant effect on visitor satisfaction. Service quality partially has a significant effect on visitor satisfaction. Therefore, the GUNPER Tasikmalaya Badminton Court must improve price perceptions and pay attention to service quality to increase visitor satisfaction at the Tasikmalaya GUNPER Badminton Court.